Strong Religion in a Secular Society: The Case of Orthodox Reformed Schools in The Netherlands - John Exalto; Gerdien Bertram-Troost (MDPI AG, 2019)
In the Netherlands, state and religious schools are equally financed by the government. Parents are free to choose a school that optimally fits their moral values as well as their idea of a good education. As a result, there is a huge variety of schools, which include those orthodox Reformed schools that form part of the so-called Bible Belt culture. We elaborate on the complex relation between this religious culture and liberal, secular society by focusing on education. Occasionally, there is severe criticism of schools based on a strong religious identity (so-called strong religious schools), especially when it comes to their allegedly inadequate contribution to citizenship education. In order to add a historical perspective and a reflection on the arguments to the debate, our central research question is: ‘How can the founding and existence of orthodox Reformed schools in the Dutch liberal and secular society be explained and justified?’ Starting with a historical explanation of why the orthodox Reformed founded their own schools in the 1920s, we elaborate on philosophical arguments that can justify the existence of orthodox Reformed schools in a liberal, secular society.